Multiple myeloma with primary manifestation in the mandible/jaw – A case report (Indian Journal of Case Reports, 2025)
Plasma cell dyscrasias are neoplastic proliferation of monoclonal plasma cells encompassing a wide range of entities. Plasmacytoma may present as one of two distinct clinical entities: Multiple myeloma (MM) and solitary plasmacytoma. MM is the most common hematological malignancy accounting for 10% of all hematological cancers. Oral lesions can be seen in up to 70% of MM cases, with the jawbone being involved in up to 30% of cases. The challenge with MM patients is that oral manifestations of myeloma can masquerade as dental or oral pain, swelling, or infection, which if not correctly diagnosed, might lead to a delay in therapy. Here, we present the case of a 45-year-old female complaining of swelling in the left lower gum and multiple loose teeth for 6 months. This case report illustrates the clinical presentation, radiographic, and diagnostic challenges encountered when MM primarily presents in a rare site such as the oral cavity.